Resistences and difficulties of a communitary police program - Muniz, Jacqueline; Larvie, Sean Patrick; Musumeci, Leonarda; Freire, Bianca (Tempo Social, 1997)
The paper draws upon data from a year long evaluation study of a community policing program in Copacabana and Leme, neighborhoods on the south side of Rio de Janeiro. Besides monitoring statistics from the Military and Civil police forces, the program included a wide variety of qualitative data. The paper describes four distinct visions of conflict, disturbance and crime which emerge from analysis of these multiple sources of data.